Tax arbitrage in government bonds: A suggested methodology with policy implications - Katz, Eliakim; Prisman, Eliezer Z (Journal of Banking & Finance, 1997)
This paper develops a geometric methodology with which to analyze the no-arbitrage condition, with special reference to tax arbitrage in government bonds. Using this methodology, it is shown that a country's bond-issuing authority might be able to painlessly avoid market equilibria which is likely to induce tax arbitrage activities. The simple bond-issuing policy which will achieve this goal is identified, and its limitations are discussed. An examination of the Canadian and Israeli bond markets shows that adopting the prescribed bond-issuing policy does not meaningfully impinge on the bond-issuing authority's ability to sell bonds.